JURIDICAL ANALYSIS OF THE APPLICATION OF ADDITIONAL PENALTIES IN FISHERIES CRIMES - Suryaputra, Muhammad Trialdy (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
Fisheries crime is a form of crime that has a multidimensional impact, both on state sovereignty, the sustainability of marine ecosystems, and national economic stability. Additional criminal regulations in Law Number 31 of 2004 concerning Fisheries, as amended by Law Number 45 of 2009, are intended to strengthen deterrence by authorizing the seizure of ships, fishing gear, and fishery products, and the revocation of business licenses. Along with the enactment of Law Number 1 of 2023 concerning the National Criminal Code, Indonesia's penal system has undergone a renewal that emphasizes proportionality, prevention, and protection of the public interest. This study aims to juridically analyze additional criminal arrangements in fisheries crimes and to examine their effectiveness in judicial practice. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that normatively, additional crimes have a strategic position as the main instrument in cutting off the economic benefits of the perpetrators, but in practice, there are still inconsistencies in implementation due to the facultative nature of the norm and the lack of optimal harmonization with national penal policies.